Nhân tố văn hóa trong đối chiếu ngôn ngữ và dịch thuật (trên ngữ liệu các thành ngữ Việt, Nga, Anh) = The cultural factors in contrastive linguistics and translation (on the material of Vietnamese, Russian and English idiomatic expressions) /Nguyễn Xuân Hòa. - Nguyễn, Xuân Hòa.
Each language has its own ways of preserving idioms. Thus, when people speaking different mother tongues communicate with one another, they must make all possible efforts to create a shared knowledge channel between the speakers and the listeners. When comparing two languages, we can see that differences between them are manifested not only in terms of structural patterns but also, more specifically, in various aspects of the specific categorization of reality of each nation. Therefore, while comparing idioms and proverbs, it is necessary to pay attention to the compilation of meanings (semantic combinations) of their parts into overall meaning to be used in real communication. In other words, when comparing idioms or proverbs of two languages, it is necessary to explore connotative meanings related to national culture of each nation.